Reduction of subclinical Salmonella infection in fattening pigs after dietary supplementation with a ß-galactomannan oligosaccharide - Andres Barranco, Sara (2015)
To assess the efficacy of a b-galactomannan oligosaccharide (ß-GMOS) for the control of Salmonella infection in fattening pigs. Three different doses (05, 3 and 2 kg ß-GMOS per ton of feed) were used during the entire period of growing in three similar and independent field trials carried out in a small fattening unit (100 pigs). Treatment was randomly assigned to half of the pens. Individual serum samples (20?25 per group) were collected at different times during the fattening period and a similar number of faecal samples during the fattening period and at slaughter. In addition, mesenteric lymph nodes were collected at slaughter. Herdcheck Swine Salmonella ELISA was used for serological analyses, the ISO 6579:2002/Amd 1 : 2007 for bacteriology and the PFGE for molecular characterization of Salmonella strains. The addition of ≥2 kg t1 of ß-GMOS to the pig diet during the entire fattening period was associated with a reduction in Salmonella prevalence, shedding and seroconversion. Feed supplementation with ß-GMOS may be a useful complementary tool for the control of salmonellosis in fattening pigs. Significance and Impact of the Study: ß-GMOS may be a complementary way of reducing Salmonella shedding and infection in fattening pigs.